The growth of the modern West Indies - Lewis, Gordon K.; Knight, Franklin W. (Kingston, Jamaica ; Miami : Ian Randle, 2004)
Provides an in-depth analysis of the forces that contributed to the shaping of the West Indian society covering the the crucial inter-war years from the 1920s to the period of the 1960s.
Introduction -- The West Indian scene -- The Caribbean background -- British colonialism: the social legacy -- British colonialism: the political legacy -- The Incubus of Crown Colony: The Leeward Islands -- The Incubus of Crown Colony: The Windward Islands -- The emergence of national society: Jamaica -- The emergence of national society: Trinidad and Tobago -- The emergence of national society: Barbados -- The emergence of national society: Guyana -- The Latin Enclave: British Honduras -- The Atlantic Perimeter: Bermuda and the Bahamas -- The problem of size: The Lesser group -- The federal venture: The formative years -- The federal venture: the road to failure -- The challenge of independence.
"Originally published in the USA 1968 by Monthly Review Press."
Includes bibliographical references (pages 495-528) and index.
NLJCols20082021
Keywords: West Indies -- History; Caribbean Area -- History; West Indies, British -- Social conditions; West Indies, British -- Politics and government; Gesellschaft; Kultur; Westindien; Politics and government; Social conditions; Caribbean Area; West Indies; West Indies -- British West Indies; Geschichte 1918-1968.; History